Prevalence of Paediatric Head and Neck Malignancies in the North Region of Brazil: A Cross-sectional Study - Emilly Silva e Silva; Marina Fadul Neves Couto; Gerlane Lima Oliveira; Cássia Alves de Lima Luna; Marco Tullio Brazão Silva; Caio De Andrade Hage; John Minh Le; Douglas Magno Guimarães (Journal of Clinical and Diagnostic Research, 2024)
Introduction: Head and Neck Cancer (HNC) ranks sixth among the most common men’s tumours. The prevalence of HNC in children has increased in several countries, and the prevalence varies worldwide. In several regions in Brazil and the world, a lack of epidemiological data records on childhood HNC is observed, demonstrating little knowledge about the demographic profile of these patients. Aim: To determine the prevalence of HNC in paediatric patients over the years at a reference centre in the North region of Brazil. Materials and Methods: A cross-sectional study was conducted with the objective of quantitatively and qualitatively analysing the prevalence of HNC in a reference oncology hospital. The electronic medical records of patients aged 0 to 19 years were reviewed at a referral centre in Northern Brazil from October 2015 to February 2022. Demographic variables, topographic location of tumours, city of origin, patient outcome, and histopathological diagnosis were collected. Results: A total of 4,113 medical records were analysed, and 126 met the criteria for analysis. Males had a higher incidence n=75 (59.52%) of HNC than females n=51 (40.47%). The age group with the highest percentage of HNC was > 4 to 9-year-old n=40 (31.74%). The most common diagnosis were lymphoma 78 (61.90%), sarcoma 22 (17.46%); carcinoma 14 (11.11%), and histiocytosis 10 (7.93%). Conclusion: In Northern Brazil, the most common tumour was Hodgkin’s lymphoma, and the most prevalent group affected were males aged > 4-9-year-old.